Echocardiography during attack of angina pectoris - Widimský, P; Gregor, P; Cervenka, V; Vísek, V (Cor et vasa, 1983)
Two patients with angina pectoris were echocardiographically examined during an attack of angina pain. In both patients, segmental asynergy of the left ventricle was present during chest pain. The echocardiographic finding before the attack and after its regression was normal. It appears that angina pectoris and an echocardiographically detectable asynergy of the left ventricle are two processes taking place almost simultaneously, their common cause being myocardial ischaemia. Wall motion abnormalities which develop during an attack of angina pectoris are fully reversible. These findings also indirectly support the assumption that two-dimensional echocardiography can practically immediately after the onset of chest pain in myocardial infarction prove asynergy of the left ventricle.
Keywords: lidé středního věku; angina pectoris; Humans; lidé; Middle Aged; srdce; Echocardiography; Angina Pectoris; Heart; echokardiografie